Guarding net effects on landings and discards in Mediterranean trammel net fishery: Case analysis of Egadi Islands Marine Protected Area (Central Mediterranean Sea, Italy) - Sardo, Giacomo; Vecchioni, Luca; Milisenda, Giacomo; Falsone, Fabio; Geraci, Michele Luca; Massi, Daniela; Rizzo, Pietro; Scannella, Danilo; Vitale, Sergio (Frontiers in Marine Science, 2023)
Discards remain among main negative impacts of fishing activities, and their reductions are strengthened by the European CFP (European Regulation 1380/2013). Trammel net fisheries appears more sustainable compared to other fishing techniques especially from an ecological viewpoint. Despite this, reports show that trammel net fisheries deliver discards quantities between 10% and 43% of total catch biomass. To supplement existing information, this current work attempts to address the discards reduction using guarding net in the small-scale fisheries of Egadi Islands MPA (western Sicily, central Mediterranean Sea). To assess the reduction of unwanted catches, forty-eight experimental fishing trials were conducted within a six month period. The experimental fishing trial employed trammel net made up of 20 panels alternated with two different net configurations. Control panels (CN) held a large outer (180 mm) and small inner (31.25 mm) meshes. Test panels (GN) with guarding net constituted 3-mesh-high (50 mm mesh size) net placed between trammel net panels and lead line. A total of 3310 individuals belonging to 106 taxa and 9 phyla were caught. Crustaceans were the most abundant unwanted catches in control panels, whereas bioconstructions occurred in guarding net panels. Discard ratios of CN and GN panels were statistically different (t value=–2,55; p < 0.05). The analysis of catch per unit effort (CPUE) showed higher catches of CN panels for both commercial and discards fractions (p < 0.05). More so, the guarding net panels caught the main discarded species 20% lower compared to control. Overall value of the catch at CN panels (€ 3.366,90) was higher total income (€ 2.043,70) using the GN panels, which suggests a significant commercial loss of 40% (p < 0.05).